Edukasi Pola Hidup Bersih dan Sehat Melalui Jajan Sehat di Sekolah Dasar Cipinang Besar Selatan 13 - Robby, Rohima; Savitri, Fitri; Sabrina, Alifa; Agustina, Ika (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Food poisoning incidents often occur in children at school. Clean and healthy living behavior needs to be fostered from an early age to prevent infectious diseases, and also to improve learning effectiveness, increase productivity and create a complete and comfortable environment. This program aims to provide counseling on clean and healthy lifestyles through healthy snacks. The method used in Community Service (PkM) activities is through direct counseling activities. Participants in this activity consisted of 35 students of SDN Cipinang Besar Selatan 13. The results of this activity show the enthusiasm and enthusiasm of students when participating in activities with the theme of Clean and Healthy Lifestyle (PHBS) which is shown from the desire of students when trying to answer questions from the speaker. This activity is expected to provide benefits both for schools and for students involved in implementing a Clean and Healthy Lifestyle (PHBS).